Augustan Rome 44 BC to AD 14 : the restoration of the Republic and the establishment of the empire - Richardson, John, 1946- (Edinburgh history of ancient Rome., 2012)
Centring on the reign of the emperor Augustus, volume four is pivotal to the series, tracing of the changing shape of the entity that was ancient Rome through its political, cultural and economic history. Within this period the Roman world was reconfigured. On a political and constitutional level the patterns of the republic, which sustained an oligarchic regime and a popularist structure, were transformed into a monarchical dictatorship in which the earlier elements continued to function. On an imperial level, the growth in Roman power reached what was virtually its apogee. In literature and the visual arts, new forms of expression, based on those of the previous generations but closely linked to the new regime, showed great achievements. In society and the economy, the effectiveness and dominance of Rome as the centre of world power became increasingly obvious.